2022
DOI: 10.1038/s41366-022-01187-z
|View full text |Cite
|
Sign up to set email alerts
|

Small fragments of hyaluronan are increased in individuals with obesity and contribute to low-grade inflammation through TLR-mediated activation of innate immune cells

Abstract: Background and aim Extracellular matrix (ECM) components released during excessive fat mass expansion are considered potential endogenous danger/alarm signals contributing to innate immune system activation. The aim of the current study was to specifically measure plasma levels of low molecular weight (LMW) hyaluronan (HA) and to evaluate its role as pro-inflammatory damage-associated molecular pattern (DAMP) on leukocyte response in the context of human obesity. Subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…The expression of low molecular weight (15–40 kDa) hyaluronan (HA) molecules is upregulated in the circulating blood of obese individuals, which causes an increased expression of pro-inflammatory cytokines such as IL-1β, IL-8, and monocyte chemoattractant protein-1 (MCP-1, or CCL2) in peripheral blood monocytes [ 61 ]. The underlying molecular mechanism study shows that those HAs induce the activation of nuclear factor kappa B (NF-κB) signaling, by regulating the phosphorylation of the α/β complex IκB kinase (IKK).…”
Section: Molecular Targets For Obesity Treatmentmentioning
confidence: 99%
“…The expression of low molecular weight (15–40 kDa) hyaluronan (HA) molecules is upregulated in the circulating blood of obese individuals, which causes an increased expression of pro-inflammatory cytokines such as IL-1β, IL-8, and monocyte chemoattractant protein-1 (MCP-1, or CCL2) in peripheral blood monocytes [ 61 ]. The underlying molecular mechanism study shows that those HAs induce the activation of nuclear factor kappa B (NF-κB) signaling, by regulating the phosphorylation of the α/β complex IκB kinase (IKK).…”
Section: Molecular Targets For Obesity Treatmentmentioning
confidence: 99%
“…Increasing evidence points to the involvement of hyaluronan and its receptors in obesity-related adipocyte hyperplasia and hypertrophy and adipose tissue metabolism [ 81 ]. An enhanced expression of hyaluronan synthase-1 was demonstrated in adipose tissue from obese patients [ 82 ]. It has been suggested that adipocyte hypertrophy contributes to adipose tissue inflammation [ 83 ].…”
Section: Pathophysiological Importance and Associated Alterations Of ...mentioning
confidence: 99%
“…It has been suggested that adipocyte hypertrophy contributes to adipose tissue inflammation [ 83 ]. Adipose tissue hypertrophy during obesity-related weight gain severely destabilizes extracellular matrix homeostasis by modifying the local oxygen supply, which in turn triggers cellular stress events and inflammation [ 82 ]. A potential role of hyaluronan in adipogenesis in vivo has been demonstrated in mouse models of high-fat diet-induced obesity [ 79 , 84 , 85 , 86 , 87 ].…”
Section: Pathophysiological Importance and Associated Alterations Of ...mentioning
confidence: 99%
See 2 more Smart Citations